Targeted Therapy and Traditional Chemotherapy in Melanoma and Cutaneous Squamous Cell Carcinoma - Ma, Vincent T.; Haring, Catherine T.; Warrier, Govind; Swiecicki, Paul L. (Facial Plastic Surgery, 2020)
Cutaneous squamous cell carcinoma (cSCC) and melanoma encompass the majority of all malignant skin cancers. There has been an increase in their incidence globally in recent decades. In cases of high-risk, unresectable, or metastatic disease; or when patient factors or preferences limit the availability of conventional surgery or radiotherapy; or a systemic therapy is often warranted. Our improved understanding of the molecular and immune pathogenesis underlying tumor growth and development has been critical in advancing cancer therapeutics. Over the past several years, several new systemic agents have been approved for both diseases. The role of cytotoxic chemotherapy is gradually waning with the introduction of targeted therapy and immunotherapy. In this article, we review the current and relevant literature and evidence of cytotoxic chemotherapy, targeted therapy, and immune checkpoint inhibitors in the adjuvant and neoadjuvant settings for cSCC and melanoma. Additionally, we describe their role in the unresectable or metastatic disease setting.
Keywords: cutaneous squamous cell carcinoma; melanoma; chemotherapy; targeted therapy; immunotherapy